Cuidado, frágil: aproximações e distanciamentos de trabalhadores de um CAPS na atenção ao suicídio - Cescon, Luciana França [UNIFESP] (2015)
This work aimed to study suicide care in a Psychosocial Care Center from Santos/SP, proposing interventions that may qualify attention to these cases. It is an intervention research with cartographic approach, in which several instruments have been used to produce data. It is intended to initially understand the organizational work process to meet this request and, for that, screening appointment records from May 2012 to December 2013 were collected, study of medical records from people with suicidal ideation and/or suicide attempt, examination of user?s appointment flow and a survey of materials about suicide. They were also carried out semi-structured interviews with health workers involved in these cases to understand their views on the subject. These materials, as well as the implication of the researcher who was part of this unit staff, were analyzed in individual and collective orientation spaces. It was found that care offers were focused on mental distress medicalization and the service organization was predominantly focused on providing medical appointments. First analyzes create questions that allowed the construction of a material that also represents a research product, called as affection box (with books, articles, movies, music and poetry) that brings different perceptions about suicide and was used on the conversation circles. It can be consulted and/or used by professionals, students and others who are interested in the subject ? available in attachment and blog. On the next phase of this research, four conversation circles were made with the team, in which the materials and systematic issues were presented and provoked new conversations that allowed to question the prevailing views on the subject and rethink work process in the unit, not only in terms of suicide care, but also for other mental suffering issues. Another important aspect is workers suffering and the medicalization of this suffering. Later, unit's psychiatrists were also interviewed, considering the importance of medical appointment and drug prescription in this service organization to meet these and other requests. This step brought new data what contributed to the expansion of this discussion. Interventions produced by this investigation appeared since the early stages and they are expressed in the leadership of these workers, who have reunited to create spaces for meeting and continuing education in order to analyze their work processes and the produced care. In this way, it aims to contribute to reflection and attention proposals for this important public health problem.